(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides a scientific analysis of cases of physical developmental delays in primary school students. The main causes of the problem are insufficient physical activity, improper nutrition, socio-economic environment, and environmental factors. Based on statistical data and scientific research, the consequences of delays behind are highlighted, and practical recommendations for eliminating these situations are given.